Arbuscular mycorrhiza confers lead tolerance and uptake in Miscanthus sacchariflorus. Issue 5 (28th May 2018) - Sarkar, Animesh; Asaeda, Takashi; Wang, Qingyue; Kaneko, Yasuko; Rashid, Md H.
ABSTRACT: The effects of an arbuscular mycorrhizal fungi (AMF) association on the growth, survival capabilities, nutrients and lead (Pb) uptake of Miscanthus sacchariflorus under different Pb concentrations were studied in the form of pot cultures. The treatments comprised inoculation or non-inoculation of the AMF, Gigaspora margarita, and the addition of three Pb concentrations to the soil (0, 100 and 1000 mg kg −1 ). The addition of Pb significantly decreased mycorrhizal colonisation. The inoculation of AMF with Pb increased chlorophyll content, Fv/Fm, total dry mass, indole-3-acetic acid (IAA), total nitrogen, and total phosphorus, whereas H2 O2 level, indole-3-acetic acid oxidase (IAAO) activity, and peroxidase (POD) activity were low compared to those in the non-inoculated treatments. Moreover, the application of AMF together with Pb doses induces concentrations of Pb in the plant, where the higher dose of Pb (1000 mg kg −1 ) induces a lower content of Pb in the aerial part of the plant but a higher content in the root. G. margarita enhanced the tolerance of M. sacchariflorus against Pb toxicity, and facilitated the accumulation of Pb in the plant roots, whereas translocation to the shoots was inhibited at the highest dose Pb (1000 mg kg −1 ). However, in contaminated soil, the Pb removal capability of M. sacchariflorus with AMF was remarkable.